RED BOOK AND ESPECIALLY VALUABLE SPECIES WOOD AND SHRUSH PLANTS UCH-KORGON FORESTRY (NORTHERN MACROSLOPE OF THE ALAY RIDGE) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Locations of species listed in the Red Book of the Kyrgyz Republic and conservationof especially valuable trees and shrubs: Fumariola turkestanica Korsh., Malus sieversii (Ledeb.)M. Roem.., Lonicera paradoxa Pojark. Amygdalis bucharica Korsh., Juniperus seravschanicaKom., J. semiglobosa Regel, Juglans regia L , Pistacia vera L.
Keywords: flora, Red Book, northern slope of the Alaj Range.